PENGEMBANGAN MEDIA PERMAINAN MONOPOLI TOPENG CIREBON DALAM BIMBINGAN KELOMPOK TENTANG KONTROL DIRI - Zahra Fania Putri; Amien Wahyudi; Siti Muyana; Hardi Prasetiawan; Mohamad Amirudin (Program Studi Bimbingan dan Konseling, FKIP Universitas Pancasakti Tegal, 2022)
Self-control is an important part of the education system according to Law No. 20 of 2003. Junior high school students often face various problems, including self-control. One of the important roles in helping students to have knowledge related to self-control is the guidance and counseling teacher with innovative, creative, and interactive media. The purpose of this research is to develop a monopoly game of Cirebon mask on self-control that can be used in guidance and counseling services, especially in group guidance services. This study uses a research and development (RnD) type referring to the research model developed by Borg and Gall. This study only uses 5 stages, namely: potential and problems, data collection, product design, product validation, and design revision. The instrument in this study used an assessment sheet to be filled out by media experts, material experts and service experts as service subjects. This research was conducted a validation test by three experts, namely material experts, media experts, and service experts. The results obtained from the material expert validation test were 93 in the very good category. The results of the media expert validation test obtained a score of 95 in the very good category. While the results of the service expert validation test obtained a value of 90.6 with a very good category. So it can be concluded that the Cirebon mask monopoly game media about student self-control is suitable for use in guidance and counseling services. Keyword: Cirebon mask monopoly game media, group guidance and self-control for junior high school students.